ANALISIS TOTAL PREDICTIVE MAINTENANCE DENGAN METODE OEE (OVERALL EQUIPMENT EFFECTIVENESS) GUNA MENINGKATKAN PERFORMA PADA MESIN HUSKY (PT. XY GEMPOL) - Wuryanto Wuryanto; Abdul Wahid (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2018)
The study was conducted with the aim of: 1. To determine the maintenance conditions and effectiveness of the Husky engine at PT. XY at present.2. To find out the effectiveness level of Husky machines at PT. XY.3. To find out the efficiency before and after the husky engine repair at PT. XY. The method used is Overall Equipment Effectiveness. After conducting research, an overall equipment effectiveness score of 90.95% is obtained. This result has exceeded the world-class standard of 85% but has not reached the company standard of 97%. It is known that the lowest value that causes this low OEE value is a performance rate of 92.8%. What causes the low-performance rate consists of machine, human, environmental, method and material factors. Human and machine factors are the most dominant factors. To improve the performance rate, improvements were made to the machine's start-up and shut-down training to the operator as well as the machine's setting parameters, the application of 5S and GMP audits and the replacement of engine spare parts according to the schedule in the manual book. The results obtained after the improvement showed an increase in performance rate to 102.02%, these results were obtained by increasing the engine cycle time from 9 seconds to 7.5 seconds.